A High Security Dynamic Secret Key Management Scheme for Wireless Sensor Networks - Lanying Li; Xin Wang (2010 Third International Symposium on Intelligent Information Technology and Security Informatics, 2010)
It's very important to find an efficient method of secret key management to guarantee secure communication in wireless sensor networks. In this paper, a cluster-based dynamic secret key management scheme has been proposed. A pairwise key has been established through OR and XOR operations in this scheme since its low energy and limited memory space of a sensor node. These OR and XOR operations not only save energy of sensors but also with high efficiency. The keys between sensors can be updated, which can strengthen the security of the wireless sensor networks. Finally, the simulation results proved that the scheme has high security and low energy cost compared with other schemes.